"De Arthetica passione" in a XVth century Italian manuscript - M.T. Navarro Salazar (PAGEPress Publications, 2011)
The author describes a 15th century Italian manuscript by Antonio Cauchoreus based on the translation of the treatise "De Arthetica passione" by Antonio Guainiero di Pauia. This manuscript, that is in the Capitular Archive of Toledo, in keeping with the method of Consilia (analysis of symptoms, definition of the cause and diagnosis), presents some practical rules to treat gout, including particular herbal remedies.